2020
DOI: 10.1111/hepr.13470
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of hepatitis B vaccination policies for healthcare workers between the USA, the UK, and Germany

Abstract: The hepatitis B (HB) vaccine is effective for the prevention of HB virus infection. It has been widely accepted that an anti‐HB surface antibody (HBs) level ≥10 mIU/mL is protective against HB virus infection. Although transient infection can occur in individuals who attain a peak level of anti‐HBs ≥10 mIU/mL after primary vaccination, long‐term follow‐up studies show that successful primary vaccination can prevent individuals from acute clinical hepatitis and chronic infection. Healthcare workers (HCWs) are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It is well documented that after primary HBV immunization, anti-HBs concentrations slowly decline and about 15-50% of vaccinated children will have low or undetectable concentrations of anti-HBs 5-15 years after vaccination [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that after primary HBV immunization, anti-HBs concentrations slowly decline and about 15-50% of vaccinated children will have low or undetectable concentrations of anti-HBs 5-15 years after vaccination [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a common agreement that a responder to the primary dose should be considered protected despite the actual antibody titer [6]. In the past several years, the international scientific community has raised a debate about the need for a booster dose [18].…”
Section: Introductionmentioning
confidence: 99%
“…28 Furthermore, students with anti-HBs antibody titers of 10 to <100 mIU/ml, being a highrisk group of health care workers, are advised one booster dose of HBV vaccine according to the United Kingdom and Germany policy for health care workers. 29 These policies consider an anti-HBs titer !100 mIU/ml a successful vaccination. Highly significant differences were observed between the mean baseline and postrevaccination antibody titers in both genders in the present study with higher levels reported postrevaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Health care staff comprise one of these groups, with a 2-10 times higher risk of infection than the general population. Transmission generally occurs through accidental exposure to patients' blood, primarily as a result of parenteral procedures [3,11,18,20,25].…”
Section: Scientific Background and Rationalementioning
confidence: 99%